PENDAMPINGAN INOVASI KUE GARPU DARI TEPUNG MOCAF SEBAGAI PENINGKATAN HASIL USAHA UMKM DI DESA WONOKERSO - Hanjar Ikrima Nanda; Reisya Alvira Harmantya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
Cassava is a commodity source of carbohydrates that is cultivated in Wonokerso Village. To increase its utilization,cassava can be modified into various types of flour such as mocaf. Modified Cassava Flour (MOCAF) is a productderived from cassava flour which uses the principle of modifying cassava cells by microbial fermentation, thendrying and grinding into mocaf. The training and assistance was carried out by the service team to innovate newproduct made from mocaf for one of the UMKM in Wonokerso Village, called the UMKM Assorted Chips